Job Search and Savings: Wealth Effects and Duration Dependence - Lentz, Rasmus; Tranæs, Torben (Journal of Labor Economics, 2005)
This article studies a risk‐averse worker’s optimal savings and job search behavior as she moves back and forth between employment and unemployment. We show that job search effort is negatively related to wealth under the assumption of additively separable utility. Consequently, job search exhibits positive unemployment duration dependence because wealth is drawn down to smooth consumption as the spell progresses. Finally, given optimal search, savings still provide imperfect insurance against income fluctuations; precautionary savings are built up during employment spells and run down during unemployment spells, but the consumption path will not be perfectly smooth over states.